1997
DOI: 10.1524/ract.1997.77.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric and Statistical Analysis of Uranium(VI) Hydrolysis at Elevated U(VI) Concentrations

Abstract: 26 UV-Vis spectra of U(VI) samples in the pH range 2.4 to 4.8 and U(VI) concentration range 6 · 10"' M to 2 · 10" 4 M in 0.1 M aqueous Perchlorate solutions are analyzed simultaneously by model free techniques, e.g. factor analysis, target rotation and non-parametric statistics. Within the investigated range of conditions, three factors only are found to be significantly contributing. UOHaq), (U0 2 ) 2 (0H)r and (U0 2 ),(0H)í are found as the relevant species. A single component spectrum of the (U0 2 )I(0H)Î s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
6
24
1
Order By: Relevance
“…Our data on uranyl hydrolysis in acidic aqueous solutions are close to Meinrath's data [19]. Based on the analysis of electronic absorption spectra of aqueous uranyl solutions at 550 nm, Meinrath concluded that this spectrum is initiated by a superposition of spectra of three uranyl species.…”
Section: Resultssupporting
confidence: 87%
“…Our data on uranyl hydrolysis in acidic aqueous solutions are close to Meinrath's data [19]. Based on the analysis of electronic absorption spectra of aqueous uranyl solutions at 550 nm, Meinrath concluded that this spectrum is initiated by a superposition of spectra of three uranyl species.…”
Section: Resultssupporting
confidence: 87%
“…Noise reduction was achieved by averaging multiple scans. Interpretation of these spectra by factor analysis [13] suggested three species, in agreement with previous results [13,14] Lifetimes are measured after excitation with a dye-laser pulse at 420 nm. Laser pulse energy was about 100 µJ.…”
Section: Methodssupporting
confidence: 89%
“…It has been shown previously that these formation constants are not in agreement with similar other assessments of U(VI) hydrolytic behaviour and also discrepant with direct speciation by using UV-Vis and laser-induced fluorescence spectroscopy [13][14][15]18,19,26].…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Hence, single component spectra of relevant hydrolysis species have been evaluated by chemometric techniques in undersaturated systems. 4,5 In these studies, only three species are found to be supported by the spectroscopic data in a pH and U(VI) concentration range, where evidence for further species has been claimed in literature -even though with considerable scatter. 6,7 0236 5731/98/USD 17.00 9 1998 Akaddmiai Kiad6, Budapest All rights ' reserved In the following, application of these UV-Vis single component spectra to solid-aqueous phase equilibrium of UO3"2H20(s) under 0.03 kPa CO 2 (air) is reported.…”
Section: Introductionmentioning
confidence: 71%